2023
DOI: 10.1186/s12890-023-02794-w
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct prednisone in community-acquired pneumonia: 180-day outcome of a multicentre, double-blind, randomized, placebo-controlled trial

Claudine A. Blum,
Eva A. Roethlisberger,
Nicole Cesana-Nigro
et al.

Abstract: Background Several trials and meta-analyses found a benefit of adjunct corticosteroids for community-acquired pneumonia with respect to short-term outcome, but there is uncertainty about longer-term health effects. Herein, we evaluated clinical outcomes at long term in patients participating in the STEP trial (Corticosteroid Treatment for Community-Acquired Pneumonia). Methods This predefined secondary analysis investigated 180-day outcomes in 785 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…That was considered statistically nonsignificant. In contrast to our study, Blum et al (32) stated that cortisone therapy is significant predisposing factor for RP with P = 0.007%. Also, much researches assessing adverse effects after short-term prescription of corticosteroids have demonstrated an increase of secondary infections even beyond day 30 (33) .…”
Section: Discussioncontrasting
confidence: 99%
“…That was considered statistically nonsignificant. In contrast to our study, Blum et al (32) stated that cortisone therapy is significant predisposing factor for RP with P = 0.007%. Also, much researches assessing adverse effects after short-term prescription of corticosteroids have demonstrated an increase of secondary infections even beyond day 30 (33) .…”
Section: Discussioncontrasting
confidence: 99%
“…A meta-analysis of 4 studies of 1000 patients with severe CAP also reported no association between low-dose corticosteroids and risk of secondary health care–associated infections in the ICU (8% vs 10%; relative risk, 0.89; 95% CI, 0.60-1.32). However, a 180-day follow-up of 727 patients enrolled in the STEP trial (corticosteroids for CAP) demonstrated a higher risk of recurrent pneumonia (8% vs 3%; OR, 2.57; 95% CI, 1.29-5.12) and secondary infections such as dermatologic, urogenital, pulmonary, intestinal, and endocardium/foreign body infections (17% vs 10%; OR, 1.94, 95% CI, 1.25-3.03) with corticosteroids . A meta-analysis of 9 studies reported a significantly lower risk of nosocomial infections in 2311 patients with COVID-19 treated with dexamethasone 12 vs 6 mg daily (absolute risk difference, −16.7 per 1000; 95% CI, −25 to −5.4; very low certainty) .…”
Section: Discussionmentioning
confidence: 99%
“…However, a 180-day follow-up of 727 patients enrolled in the STEP trial (corticosteroids for CAP) demonstrated a higher risk of recurrent pneumonia (8% vs 3%; OR, 2.57; 95% CI, 1.29-5.12) and secondary infections such as dermatologic, urogenital, pulmonary, intestinal, and endocardium/ foreign body infections (17% vs 10%; OR, 1.94, 95% CI, 1.25-3.03) with corticosteroids. 71 A meta-analysis of 9 studies reported a significantly lower risk of nosocomial infections in 2311 patients with COVID-19 treated with dexamethasone 12 vs 6 mg daily (absolute risk difference, −16.7 per 1000; 95% CI, −25 to −5.4; very low certainty). 25 However, data from retrospective studies and case series suggested that patients with COVID-19 treated with high doses of corticosteroids were at increased risk of nocardiosis, 72 mucormycosis, and pulmonary aspergillosis.…”
Section: Adverse Effects and Complications Of Corticosteroid Treatmentmentioning
confidence: 99%